Gestión administrativa-tributaria Comercial Franklin del Cantón Babahoyo durante el año 2019 - Chica Carriel, Lisbeth Abigail (2020)
The objective of this case study is to describe the commercial administrative-tax applications and techniques currently used in its general management, the company as an economic and social entity has an interest in being efficient and adapting to the changes that are triggered in the environment in the social and economic order. Administrative management allows optimizing the execution of the process to increase the quantity and efficiency, which is essential because it supports the empowerment of the tasks, forming a network of functions on which the activities are based and related, they are oriented towards complying with business objectives. Its income is generated for the most part by sheets, awnings, kitchen shelves and pillows. The franklin commercial his strategy of a business model is to earn more money with each market segment, Profitability ratios are presented buying the two years of activity for To faithfully comply with the stated purpose, the entity has always complied with all the provisions of current Ecuadorian legislation, such as delivery of sales receipts and being a withholding agent, since it must keep accounting and listen to the reforms of laws issued by the regulatory body . The applied methodology is descriptive since it is used to collect, summarize, present, analyze the results of the observations, and it is concluded that the company is being inefficient in the period studied unlike the previous year and that there must be a better organization within the internal activities in the company so that there are no decreases in sales and combine the company's needs with the strengths, interests, and motivations of the employees.